Grammar, gesture, and meaning in American Sign Language - Liddell, Scott K., 1946- (Cambridge University Press, 2003)
In sign languages of the deaf, now recognized as fully legitimate human languages, some signs can meaningfully point toward things or can be meaningfully placed in the space ahead of the signer. This book focuses on American Sign Language to examine the grammatical and conceptual purposes served by these signs.